O’RTA OSIY BRONZA DAVRI CHORVADOR QABILALARINING ETNOARXEOLOGIYASI OID ASARLAR TAHLILI - Begimqulov Behruz, Javohir Ergashov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides information about the Bronze Age culture of the Zarafshan oasis, the history of the study of the Bronze Age monuments of the Zarafshan oasis.